Report of the Task Force on Eco-Development Plan for Goa - Planning Commission (Planning Commission, 1982)
The district of Goa is one of the three discontinuous land blocks, which together constitute the Union Territory of Goa, Daman and Diu. It covers an area of 3701 sq.km., or 97% of the total area, and a population of 10.03 lakh persons, or 93% of the total population of the Union Territory. The district is generally characterised by hilly terrain.
Government of India, Planning Commission